Rituximab, Omalizumab, and Dupilumab Treatment Outcomes in Bullous Pemphigoid: A Systematic Review - Cao, Peng; Xu, Wenjing; Zhang, Litao (Frontiers in Immunology, 2022)
Background Bullous pemphigoid (BP) is the most common autoimmune subepidermal bullous disease of skin. First-line treatment systemic corticosteroids may cause serious adverse events. Rituximab, omalizumab, and dupilumab should be explored as alternative treatment options to improve outcomes. Objective To systematically review rituximab, omalizumab and dupilumab treatment outcomes in BP. Methods A PubMed, Embase, Web of Science and Cochrane library search were conducted on March 10, 2022, to include 81 studies using Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Results Use of rituximab(n=125), omalizumab(n=55) and dupilumab(n=37) were reported in 217 patients with BP. Rituximab led to complete remission in 71.2% (n=89/125) and partial remission in 23.2% (n=29/125) of patients within 5.7 months, with a recurrence rate of 20.0% (n=25/125). 8.8% (n=11/125) of patients died and infection (6.4%, n=8/125) as the most common adverse event. Omalizumab led to complete remission in 67.3% (n=37/55) and partial remission in 21.8% (n=12/55) of patients within 6.3 months, with a recurrence rate of 5.5% (n=3/55). 1.8% (n=1/55) of patients died and thrombocytopenia (1.8%, n=1/55) as the most common adverse event. Dupilumab led to complete remission in 67.6% (n=25/37) and partial remission in 18.9% (n=7/37) of patients within 4.4 months of treatment without reported adverse events, with a recurrence rate of 5.4% (n=2/37). Conclusions Rituximab, omalizumab and dupilumab have similar clinical benefit for patients with BP. However, rituximab resulted in higher recurrence rates, adverse events rates and mortality rates.